Healthcare with a Smart Biomedical App - Koirala, Aavanish; Subedi, Sameer (International Journal on Engineering Technology, 2025)
The "RFID-Based Quick Registration and Biometric Recognition System" is an advanced, technology-driven initiative designed to address critical challenges in patient registration, data management, and healthcare service delivery, particularly in resource-constrained regions like Nepal. This innovative system integrates RFID (Radio-Frequency Identification) technology with biometric authentication to create a seamless, secure, and efficient process for patient identification and data retrieval. When a patient’s RFID card is scanned, their complete medical history, personal details, and treatment records are instantly accessed from a centralized, cloud-based database, enabling healthcare providers across Nepal to retrieve critical information in real-time, regardless of geographic location. The inclusion of biometric recognition ensures robust security, safeguarding sensitive patient data against unauthorized access and ensuring compliance with privacy regulations. In rural areas of Nepal, where healthcare infrastructure is often limited, this system holds immense significance by reducing the dependency on manual record-keeping, minimizing errors, and significantly cutting down patient waiting times. It also facilitates better coordination among healthcare facilities, enabling timely diagnosis and treatment, especially for patients referred from remote areas to urban centers. Furthermore, the system supports telemedicine initiatives, allowing healthcare professionals in rural clinics to consult with specialists in urban hospitals by providing instant access to patient data. By streamlining administrative processes, improving data accuracy, and enhancing inter-hospital communication, this project aims to bridge the gap between urban and rural healthcare services, promote equitable access to medical care, and lay the foundation for a modern, interconnected healthcare ecosystem in Nepal. Its implementation has the potential to transform healthcare delivery, improve patient outcomes, and contribute to the overall development of the nation’s healthcare infrastructure.